Effortful control, exposure to community violence, and aggressive behavior: Exploring cross‐lagged relations in adolescence. Issue 6 (11th June 2017) - Esposito, Concetta; Bacchini, Dario; Eisenberg, Nancy; Affuso, Gaetana
Abstract : Self‐regulation processes and violent contexts play an important role in predicting adolescents' aggressive behavior; less clear is how all three constructs are linked to each other over time. The present study examined the longitudinal relations among adolescents' self‐reported effortful control (EC), exposure to community violence, both as a witness and as a victim, and aggressive behavior. Participants were 768 Italian adolescents (358 males) living in a high‐risk context, with a mean age at T1 of 11 years in the younger cohort and 14 years in the older cohort. In a four‐wave cross‐lagged panel design, low EC was a strong predictor of aggressive behavior across each time point, whereas aggressive behavior was found to positively predict adolescents' violence exposure both as witnesses and victims. Some evidence of transactional relations was also found between adjustment problems and exposure to community violence and between EC and externalizing problems. Moreover, EC was indirectly related to exposure to violence through externalizing problems, and mediated the relation of witnessing community violence to aggression, thus supporting the view that top‐down regulatory processes play a complex role in the development of violence and other externalizing problems. The importance of considering interventions that take in account these complex relations is discussed.